Una breve riflessione sulla complessità della pedagogia oggi. Tra molte specializzazioni e visione unitaria/critica comune - Franco Cambi (Studi sulla Formazione)
The introductory note is an invitation to reflect on the complexity of pedagogical knowledge, which postulates the emergence of a unity consciousness capable of raising the question of the purpose of the educational action as well as of giving space and voice to different perspectives of analysis in constant interchange, in the awareness of the peculiarity of discursive structures.